Novel quaternized mesoporous silica nanoparticle modified polysulfone-based composite anion exchange membranes for alkaline fuel cells. Issue 54 (13th June 2015) - Liu, Lingdi; Tong, Cuiyan; He, Yao; Zhao, Yanxu; Hu, Bo; Lü, Changli
<x xml:space="preserve">Abstract</x> A polysulfone-based composite membrane with QMSNs showed improved conductivity, good morphologies without phase separation, acceptable mechanical properties, and alkaline and oxide resistance, opening up a new way to fabricate organic–inorganic composite AEMs.